Sowing time affecting the development of common bean cultivars in Lichinga, Province of Niassa, Mozambique - Carvalho, Maria da Conceição Santana; NASCENTE, ADRIANO STEPHAN; Barbosa, Gilvan Ferreira; Mutadiua, Celso Américo Pedro; Denardin, José Eloir (Revista Ceres, 2017)
The demonstration of yield potential of crops depends on genetic factors, favorable conditions of environment, and management. The sowing time can significantly affect the common bean grain yield. The aim of this research was to study the behavior of Brazilian cultivars and sowing times on the yield components and grain yield of common bean grown in the environmental conditions of Lichinga, Province of Niassa, Mozambique. The field trial was performed for two growing seasons, using the experimental as a randomized block in factorial 5 x 3 x 2, with four replications. The treatments consisted of the combination of five common bean cultivars (BRS Pontal, BRS Agreste, Perola, and BRS Requinte, developed by Brazilian Agricultural Research Corporation (Embrapa), and a local variety, Encarnada) with three sowing dates (beginning of the rainy season, and 15 and 30 days after), during two growing seasons. The Brazilian cultivar of common beans BRS Pontal was the most productive in all sowing times, followed by BRS Agreste, which was not the most productive only in the second sowing time of 2013/2014 growing season. The cultivar Encarnada, from Mozambique, was the less productive cultivar in all sowing times and in all growing seasons. The best sowing time for common bean cultivars is in the beginning of the rainy season. The use of technologies such as use of seeds of new cultivars, proper sowing time, fertilization, and control of weeds allow significant increase of common bean grain yield in Lichinga, Mozambique. Keywords: Phaseolus vulgaris